1997
DOI: 10.1021/bi971060t
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure of the 205−316 C-Terminal Fragment of Thermolysin. An Example of Dimerization Coupled to Partial Unfolding

Abstract: The solution structure of the C-terminal fragment 205-316 of thermolysin has been determined by 1 H-NMR methods. The fragment forms a dimer in which each subunit has two different regions: the largely disordered N-terminal segment 205-260 and the structurally well-defined segment 261-316. The structured part of each subunit is composed of three helices and is largely coincident with the corresponding region in the solution structure of the dimer formed by the shorter fragment 255-316, which in turn coincides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…26 NMR measurements on 205− 316Th confirmed the disordered N-terminal region (approximately residues 205−261) and a folded and nativelike helical structure in the C-terminal region. 51,52 Overall, the results of the derivatization of Gln and Lys residues of 205−316Th with TGase correlate with those of limited proteolysis, because TGase and proteases attack the fragment substrate at its disordered N-terminal region (see Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…26 NMR measurements on 205− 316Th confirmed the disordered N-terminal region (approximately residues 205−261) and a folded and nativelike helical structure in the C-terminal region. 51,52 Overall, the results of the derivatization of Gln and Lys residues of 205−316Th with TGase correlate with those of limited proteolysis, because TGase and proteases attack the fragment substrate at its disordered N-terminal region (see Figure 4B).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…The C-terminal fragment 205/206–316 is capable of folding into a nativelike structure in a manner independent of the rest of the polypeptide chain, thus possessing protein domain properties. Here, we explored the TGase modification at both Gln and Lys residues of fragment 205–316, containing in its amino acid sequence seven Gln and seven Lys residues (Figure S1 and Table S1 of the Supporting Information). Analysis by RP-HPLC and ESI-MS of the reaction mixture with DC after reaction for 6 h showed that the N-terminal Met can be partly removed during the reaction (Figure A), as shown by the ESI-MS data (Table S7 of the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3U, in salmon) ( 24 ), whereas its alternative delimits a domain that has been shown to be able to fold partially (Fig. 3U, in green cyan) ( 25 ). Another example is α-lactalbumin (PDB: 1a4v), which is annotated as a one-domain protein in CATH, SCOP, ECOD, and Pfam, whereas our algorithm isolates an α-helical domain in its best alternative assignment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 These domains seem to have differential stability against physical and chemical perturbations and, in addition, certain partial sequences of these domains are known to fold autonomously under moderate conditions. [7][8][9][10] We have reported the effects of high pressure on TLN activity and spectroscopic properties over a range of temperature and pressure. [4][5][6] The pressure-induced spectroscopic changes of TLN were explained by a simple two-state transition model, accompanied with a large and negative reaction volume change, ∆V.…”
mentioning
confidence: 99%